Pengaruh Strategi Pembelajaran Spontaneous Group Discussion (SGD) Terhadap Kemampuan Berpikir Kritis Matematis Siswa - Simamora, Lambok; Hernaeny, Ulfah (Jurnal Gemaedu, 2019)
The purpose of this study was to find out whether there was an influence of students' critical thinking skills using the Spontaneous Group Discussion learning strategy. The research method used in this study is quasi-experimental with a total sample of 30 groups, taken using the Proportionate Stratified Random Sampling technique. Test requirements for data analysis used are normality test, homogeneity test, hypothesis test.. From the hypothesis test the t test shows that at a significant level of 5%, it means that H0 is rejected and H1 is accepted because of tcount> t table. Which means that students 'mathematical critical thinking skills taught with Spontaneous Group Discussion learning strategies are not the same as students' critical thinking skills taught by using the Group Investigation learning strategy